If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 1) + -1 = 11 Reorder the terms: 2(1 + x) + -1 = 11 (1 * 2 + x * 2) + -1 = 11 (2 + 2x) + -1 = 11 Reorder the terms: 2 + -1 + 2x = 11 Combine like terms: 2 + -1 = 1 1 + 2x = 11 Solving 1 + 2x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 11 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 11 + -1 2x = 11 + -1 Combine like terms: 11 + -1 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| c=38.34+0.50 | | 5x-2(x-3)=4x+15 | | 11d-10=6d | | N-6n= | | 4m^2n+(-m^2n)=0 | | 4m^2n+(-m^2n)= | | 0.1*x+0.25(5x)=5.25 | | log=0.45 | | 0.85x=612 | | (6x-10)+(6x+10)=18 | | 5(7x+1)=5+2x | | 2(x-7)+3x-1=4x+3 | | 2x+x+9x=3+35+2-4 | | 87b+17b= | | 20x-5x+4=15x-4 | | 25t=25t+5 | | 3x-a=b+a | | -81r+73r= | | g(x)=x^2+22x+12 | | 8x+5=2x-5 | | 7x+6=-12 | | 6a^2+19a+15= | | Y+z=108 | | 8-88n-45n= | | 42=2(x+3)+2(x-12) | | Y=(3x^2-3x+6)*2 | | 2y+3y-5x+2x= | | n+3=q*n | | 42=2(x+3)+(x-12) | | -9(x+2)=16x-3-15x | | -60x^2-77x=0 | | 2[x+1]-1=11forx |